2024
DOI: 10.3390/pathogens13010093
|View full text |Cite
|
Sign up to set email alerts
|

The Roles and Interactions of Porphyromonas gingivalis and Fusobacterium nucleatum in Oral and Gastrointestinal Carcinogenesis: A Narrative Review

Bing Wang,
Juan Deng,
Valentina Donati
et al.

Abstract: Epidemiological studies have spotlighted the intricate relationship between individual oral bacteria and tumor occurrence. Porphyromonas gingivalis and Fusobacteria nucleatum, which are known periodontal pathogens, have emerged as extensively studied participants with potential pathogenic abilities in carcinogenesis. However, the complex dynamics arising from interactions between these two pathogens were less addressed. This narrative review aims to summarize the current knowledge on the prevalence and mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…Individuals consuming a high quantity of alcohol relentlessly promote dysbiosis of the oral microbiome [78] and encourage periodontal pathogenic microbes' accumulation [79] and tooth pocket formation more than non-alcoholics [10]. Porphyromonas gingivalis and Fusobacteria nucleatum are the most notorious periodontal pathogenic microbes [80]. It has been reported that the accumulation of these pathogens ( P. gingivalis and F. nucleatum) was substantially higher among heavy alcoholic drinkers than in non or occasional alcoholics [28,81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals consuming a high quantity of alcohol relentlessly promote dysbiosis of the oral microbiome [78] and encourage periodontal pathogenic microbes' accumulation [79] and tooth pocket formation more than non-alcoholics [10]. Porphyromonas gingivalis and Fusobacteria nucleatum are the most notorious periodontal pathogenic microbes [80]. It has been reported that the accumulation of these pathogens ( P. gingivalis and F. nucleatum) was substantially higher among heavy alcoholic drinkers than in non or occasional alcoholics [28,81,82].…”
Section: Discussionmentioning
confidence: 99%
“…As teeth are required for eating and communication, tooth loss results in physical health risks, including undernutrition and sarcopenia, as well as social frailty [4][5][6]. Furthermore, these bacteria are associated with various systemic diseases [7,8], including heart disease [9], respiratory infections [10], diabetes [11], tumors [12], brain disease [13], and risk of poor pregnancy outcomes [14]. Therefore, they significantly impact physical and mental health.…”
Section: Introductionmentioning
confidence: 99%